Implementasi Pembelajaran PjBL Berdifferensiasi Untuk Mengembangkan Berpikir Kreatif Siswa Dalam Merancang Pembangkit Tenaga Listrik Melalui Canva Pada Siswa Sekolah Dasar - Zulkifli, Arif; Sudarti; Prihandono, Trapsilo (Jurnal Pendidikan dan Pengajaran, 2025)
The results of the 2022 International Student Assessment (PISA) indicate that Indonesian students' creativity still requires serious attention. Therefore, this study aims to examine the implementation of differentiated PjBL learning to develop students' creative thinking skills in designing a power plant using Canva in elementary school students. This research was conducted experimentally using a "Pretest Post-test Control Design" design. The treatment was the implementation of differentiated PjBL learning with a project to design a power plant using Canva in class 4A (28 students), and the control was class 4B (28 students) with the same project but learning without differentiated PjBL. Measurement of students' creative thinking skills was carried out through pretests and post-tests covering indicators of fluency, flexibility, originality, and elaboration. The results of the One-Way ANOVA analysis followed by LSD showed that the pretest between the experimental and control groups did not differ significantly. However, the post-test scores of the experimental group were significantly higher than those of the control group. The results of the Mann-Whitney analysis of all indicators of students' creative thinking abilities prove that the pretest scores between the experimental group and the control group for all indicators are not significantly different. However, the post-test scores of the experimental group for all indicators are significantly higher than the control group. It is concluded that the implementation of differentiated PjBL learning is significantly able to develop students' creative thinking abilities in designing power plants through Canva in Elementary School Students.